Doris James ([Kingston, Jamaica] : Planters' Punch, 1930)
Miss Doris James, a well known vocalist at concerts, [1930]
Keywords: James, Doris; Chinese - Jamaica - History; Chinese - Jamaica; Singers - Jamaica